Chapter The Administration of Sacred Time in Hittite Anatolia - Barsacchi, Francesco Giuseppe (Studia Asiana, 2023)
The nature of the administration of sacred time in Hittite Anatolia represents a complex problem, which has received little attention until recent years. This paper provides an overview of the topic, reconsidering the Hittite religious calendar as a whole and analysing some of the main issues connected with the Hittite calendrical system, such as the problem of the beginning of the year, the lunar nature of the Hittite month and the alleged existence of a system of intercalation.